Pengaruh Financial Distress, Firm Size, Leverage, dan Ceo Retirement terhadap Prudence (Studi Empiris pada Perusahaan Sektor Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia tahun 2019-2022) - Ahmad Sovi Amrillah; Zulfikar, Zulfikar (DINASTI RESEARCH, 2024)
Prudence is a conference of accounting conservatism or which means the principle of prudence in recognizing income or assets and expenses that can result in shrinking the profits generated by a company in order to reduce the risk of uncertainty in the future. This study aims to examine the factors that affect prudence in food and beverage sector companies on the Indonesia Stock Exchange in 2019-2022. The sampling technique used in this study is purposive sampling. A total of 97 companies have met the criteria as an observation unit. The method of analysis used is multiple linear regression analysis. The results provide empirical evidence that financial distress, firm size, leverage, and ceo retirement affect prudence.